High-brightness electron injectors for high-duty cycle X-ray free electron lasers - Sannibale, Fernando (Frontiers in Physics, 2023)
The successful development in the last two decades of X-ray free electron lasers (FELs) with their revolutionary brightness performance has been tightly dependent on the parallel development of electron guns and injectors capable of providing the high-brightness electron beams required by FELs lasing at these short wavelengths. The ultimate brightness delivered by a linear accelerator (linac) is already set at its injector and the remaining part of the accelerator can be only designed to preserve the injector performance. The technology to be used for the accelerator part of an X-Ray FEL strongly depends on the duty-cycle at which the FEL operates. Normal-conducting, room-temperature, copper-based radiofrequency (RF) technology is typically used for low duty-cycles of up to approximately 10-3. For higher duty-cycles and up to continuous wave (CW) operation, the linac must rely on superconductive RF technology because, with the higher duty-cycle, the increasingly higher power dissipated in normal conducting RF structures becomes excessive for the warm technology. The situation changes in the lower energy part of the accelerator, where injector schemes, based on direct current, normal-conducting, and superconducting RF electron guns, are demonstrating the beam quality performance required by high-duty-cycle X-ray FELs. In this paper we start with a description of the requirements for such injectors, followed by an overview of the pursued technologies and schemes, and by a discussion on the main differences in terms of beam dynamics between low and high duty-cycle injectors.